Analisis Pengaruh Citra Merek, Kepercayaan Merek dan Kualitas Produk Terhadap Keputusan Pembelian Sepatu Specs (Studi Kasus Pada Konsumen Sepatu Specs Di Kota Lombok Timur) - Muh Hasban Wadi; Muinah Fadhilah; Lusia Tria Hatmanti Hutami (Universitas Batanghari, 2021)
This study aims to determine the effect of brand image, brand trust and product quality in influencing consumer purchasing decisions of specs brand sport shoes and also to determine wich factors have the greatest influence on consumer purchasing decisions of specs brand sports shoes. The study took a sample of 100 respondents to be examined using nonprobability sampling method and by using the incidental sampling technique. The data analisys used in this research is Multiple Linier Regression Analysis. Before the regression analysis was carried out, there were several stages of testing which were carried out, including the validity test and the reliability test. Then the classical assumption tests were carried out including normality test , multicolonierity test, heteroskedastisity test, individual parameter significance test (t-test), simultaneous significance test (F-test) and determination coefficient test (R2).